KONSEP SPASIAL PERSAMPAHAN 1C-2FT.RSL DAN PERKEBUNAN ENERGI JATROPHA CURCAS, KOMBINASI KONSEP UNTUK MEWUJUDKAN ECO-CITY DI INDONESIA - Sutanto, HMHB Henky (Jurnal Teknologi Lingkungan, 2006)
The Tropical Eco-City Concept brings ideas of the possibility to achieve 11and 12 targets of the Millennium Development Goal in tropical humid climate such as Indonesia by continually overcome the challenges of fresh water supply and a waste free community environment. Maintaining quality and quantity of fresh water supply requires rehabilitation of critical land on both rural and urban riverbank area in waste dumping issue.The waste production continuous process need to be balance by continuous waste treatment system facilities. The term “waste final dumping” for final dumping area has to be changed to the term “waste final treatment” as a foundation of waste final treatment area which more beneficial, continually and environmentally friendly. Sanitary landfill technology concept is not a guarantee for continuous operation, whereas reusable sanitary landfill technology concept has to be applied and appropriately included in land use planning structure of Eco-City.